2021
DOI: 10.48550/arxiv.2105.03066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broadband Spectral and Timing Properties of MAXI J1348-630 using AstroSat and NICER Observations

V. Jithesh,
Ranjeev Misra,
Bari Maqbool
et al.

Abstract: We present broadband X-ray spectral-timing analysis of the new Galactic X-ray transient MAXI J1348-630 using five simultaneous AstroSat and NICER observations. Spectral analysis using AstroSat data identify the source to be in the soft state for the first three observations and in a faint and bright hard state for the next two. Quasiperiodic oscillations at ∼ 0.9 and ∼ 6.9 Hz, belonging to the type-C and type-A class are detected. In the soft state, the power density spectra are substantially lower (by a facto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Belloni et al (2020) studied the energy dependence of the fractional rms and phase lags of the type-B QPO using NICER data, and García et al (2021) successfully fitted them simultaneously with a twocomponent Comptonisation model. Jithesh et al (2021) studied the energy dependence of the fractional rms of a type-C QPO using simultaneous AstroSat and NICER observations. They found that the rms of the QPO fundamental is nearly energy independent, while the rms of the subharmonic decreases with energy.…”
Section: Introductionmentioning
confidence: 99%
“…Belloni et al (2020) studied the energy dependence of the fractional rms and phase lags of the type-B QPO using NICER data, and García et al (2021) successfully fitted them simultaneously with a twocomponent Comptonisation model. Jithesh et al (2021) studied the energy dependence of the fractional rms of a type-C QPO using simultaneous AstroSat and NICER observations. They found that the rms of the QPO fundamental is nearly energy independent, while the rms of the subharmonic decreases with energy.…”
Section: Introductionmentioning
confidence: 99%